Impact of anxIety on self-perceIved oral health among medIcal students - Rakic, Jovan; Stepovic, Milos; Jovanovic, Nikola (Medicinski časopis, 2025)
Background: Oral health can affect mental health in many ways, and vice versa. Anxiety significantly impact the oral health and can lead to gum disease, cavities, dry mouth and bruxism and can cause bad oral health habits. Aims of our study were to investigate the prevalence of anxiety among medical students and to determinate the impact of anxiety on oral health habits and self-perceived oral health. Methods: This study presents cross-sectional study. It included the medical students from the Faculty of Medical Sciences, University of Kragujevac, Serbia. The Zung Self-Rating Anxiety Scale (SAS) was used to quantify anxiety levels and Oral Health Questionnaire for Adults was used to assess the self-perceived oral health. Data was analysed using the SPSS software, chi-square test was performed to determinate correlation between categorical variables, and Bonferroni analysis was perform to identify the precise significance between groups. Results: The assessment of the self-perceived anxiety showed that 39% of students had symptoms of anxiety. Significant positive correlation was found between anxiety and gender and self-perceived gum condition. Significant negative correlation was found between anxiety and ashamed because of teeth, avoid smiling and using dental floss. The post hoc Bonferroni analysis revealed that women exhibited anxiety more often than men, better gum health was linked to lower anxiety, embarrassment about teeth or avoiding smiling was associated with higher anxiety, and unexpectedly, flossing was more common among anxious participants. Conclusion: The influence of anxiety on oral health is not sufficiently recognized a. We found high prevalence of anxiety among medical students and determined correlation with certain oral health aspects. Medical students are vulnerable group and promotion and preventive programs should be more available.